2021
DOI: 10.14712/18059694.2021.27
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Children with Leptin Receptor Gene Polymorphisms

Abstract: Introduction: The study of single nucleotide polymorphisms (SNPs) of the leptin receptor gene (LEPR) based on next generation genomic sequencing (NGS) data is becoming an increasingly important aspect of diagnosis, treatment and prevention of both metabolically healthy (MHO) and metabolically unhealthy obesity (MUO) phenotypes. Material and methods: 35 obese children 6-18 years old were examined by the NGS method with bioinformatic analysis. The main group (n = 18) was formed by children with MUO, according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, the included studies on LEPR gene polymorphisms had inadequate samples resulting in inadequate statistical processing. Thus, the present negative results are still underpowered and further clarification may be obtained from studies with a larger number of subjects (24,25).…”
Section: Discussionmentioning
confidence: 77%
“…However, the included studies on LEPR gene polymorphisms had inadequate samples resulting in inadequate statistical processing. Thus, the present negative results are still underpowered and further clarification may be obtained from studies with a larger number of subjects (24,25).…”
Section: Discussionmentioning
confidence: 77%
“…Over the past decades, due to the pandemic nature of the spread of obesity, the problem of its treatment and prevention of metabolic disorders in children has been in the focus of medical community [22]. Evidence has now been obtained that a sedentary lifestyle, excessive consumption of high-calorie foods, sleep disorders and genetic predisposition cause a high risk of developing polygenic obesity [2]. Mutations of genes involved in the regulation of appetite, of the activity of hedonic pathways, the formation of food preferences, carbohydrate and fat metabolism, as well as the development of adipocytes, the distribution of adipose tissue in the body may predetermine excessive accumulation of fat [1,4,16,32].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that HTN is a major risk factor for T2DM[ 7 ]. One-third of HTN patients also have T2DM and are at an increased risk of cardiovascular disease and mortality[ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These predictions imply that the rs1137101 mutation may influence protein structure and have an impact on protein function. Previous studies have associated rs1137101 (Gln223Arg) with obesity, cancer, HTN and DM[ 9 , 19 , 20 ]. It also has been shown to be a risk factor for HTN and T2DM in the Chinese population[ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%